Galectin-Levels Are Elevated in Infants Born Preterm Due to Amniotic Infection and Rapidly Decline in the Neonatal Period - Faust, Kirstin; Freitag, Nancy; Barrientos, Gabriela; Hartel, Christoph; Blois, Sandra M. (Frontiers in Immunology, 2021)
Galectin (gal)-1, -3 and -9 are members of a family of glycan binding proteins that mediate complex interactions between decidual, inflammatory and trophoblast cells modulating several processes during gestation, control of the maternal immune system and parturition. Their immunomodulatory role in preterm birth and postnatal expression in preterm infants is unknown. We performed a single center prospective study of 170 preterm infants with a gestational age below 35 weeks. Peripheral venous blood samples were collected during the neonatal period and galectin-1, -3, and -9 were determined by ELISA. We noted a strong decline of circulating gal-1 and -3 levels but not gal-9 from birth to day 7 of life. There was an inverse correlation of gal-1 and -3 levels at birth with gestational age. Gal-1 levels were remarkably increased in infants born to amniotic infection syndrome (AIS), which was also observed for gal-9 levels. Infants who developed early-onset sepsis had higher levels of gal-3 at day 1 as compared to unaffected infants. Our observational data imply that galectin-1, -3 and -9 levels are elevated in preterm infants born in an inflammatory milieu such as AIS or EOS. Future studies need to address whether galectins mediate inflammation-induced preterm birth and could therefore be a target for clinical trials.